Effects of Non-Uniform Heat Source-Sink and Nonlinear Thermal Radiation on MHD Heat and Mass Transfer in a Thin Liquid Film - Saha, Prasenjit (Communications in Mathematics and Applications, 2023)
This paper describes the non-uniform heat source/sink effect on MHD heat and mass transfer of a thin liquid film taking nonlinear thermal radiation over a permeable unsteady stretching surface. Boundary conditions are taken as convective type. Similarity transformation are used to convert unsteady boundary layer equations to a system of non-linear ordinary differential equations. For the presence of nonlinear thermal radiation term in the energy equation the momentum, energy and mass-diffusion equations are highly non-linear. Thus, we can not be solved the problem analytically. To solve the problem we use numerical Runge-Kutta-Fehlberg method with shooting technique. Shooting technique helps us to determine the unknown initial condition. The effect of various parameters like Prandtl number, Schmidth number, source/sink parameters, radiation parameters, magnetic parameter, unsteadiness parameter are shown and discuss here. Some numerical results are compare in a table with previous work. It is found that increase in space dependent heat source/sink parameter and temperature dependent heat source/sink parameter decreases temperature gradient. Thermal radiation decrease the cooling rate of the thin liquid film, also increase in magnetic parameter decreases velocity distribution and increase in the temperature and concentration gradients.
Keywords: Magnetohydrodynamic; Non uniform heat source-sink; Thin liquid film; Thermal radiation; Similarity transformation